Performance Evaluation of Boric and Silicic Acid Treatment in Plywood by Shear Strength - Bhatt, Shweta; Tripathi, Sadhna; Khali, D. P. (Indian Forester, 2017)
Plywood plays a major role in consumption of wood panels in India due to its wide applicability in structural as well as nonstructural purposes. Their extensive uses in outdoor purposes create the favourable conditions for fungal attack, thus required external protection by wood preservatives. The major issue come through treatment of plywood is compatibility of preservative with the adhesive used. In the present study, plywood was treated with boric acid and silicic acid separately and in different combinations by veneer treatment method. Three concentrations i.e. 2%, 3% and 4% of each chemical and their combinations were used to treat plywood. The compatibility of these chemicals was evaluated in plywood by testing glue shear strength (GSS) in dry as well as in wet state. The study revealed that boric acid poorly affected the GSS of plywood in both test states, whereas silicic acid treated plywood performed best. Plywood treated with combinations of boric and silicic acid had shown improved shear strength and passed the minimum criteria of Boiling Water Resistant grade plywood.